Shelf-life of traditional white soft cheese (kesong puti) with added oregano and garlic - Isleta, Kristina P.; Cornago, Djanna F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
The effect of the addition of garlic and oregano to the shelf life of white soft cheese (kesong puti) had been studied. Physicochemical, microbiological and sensory properties of control kesong puti, kesong puti with garlic and kesong puti with oregano stored at 5°C were analyzed for a period of 17 days. Throughout storage, a general increasing trend in the %whey expulsion, compressibility, b' values, titratable acidity and lactic acid bacteria count was observed for all cheese samples. A general decreasing trend, on the other hand, was observed in terms of weight and crude protein content of the samples. L* values, aw, pH and total plate count throughout storage showed differences in trends among the cheese variants. There were significant differences in %whey expulsion, weight, L* and b* values and pH of the control samples with that of cheeses with treatment. The shelf-life of the control sample is 8 days based on microbial count. Oregano extended the shelf-life of kesong puti by one week. The kesong puti with garlic was still acceptable even at Day 17. Kesong puti with garlic showed a higher mean score xviii in terms of overall acceptability, appearance, flavor and texture compared to kesong puti with oregano. However, consumer preference between treated samples was insignificant. In order to improve the sensorial properties of the kesong puti with garlic and oregano, the use of essential oils in exchange of using the fresh or powder form of the product is being recommended.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Cheese -- Varieties -- Philippines; Kesong puti